Field notes contributed by Dean Mosman, Elkhart, Iowa, winter 1983-1984 - Mosman, Deanet al (1983)
Field notes were contributed by Dean Mosman, Elkhart, Iowa, winter 1983-1984. He documented sighting a Northern Goshawk. Other species names on the list preceded by a red dash were: Rufous-sided Towhee, Pine Siskin, and Harris' Sparrow. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed